RELATIONSHIP BETWEEN ORAL FLUID PH, DENTAL CARIES AND ENAMEL RESISTANCE IN CHILDREN - Chukhray, N.L.; Mashkarynetz, O.O.; Chemerys, O.M.; Musij-Sementsiv, Kh.H. (World of Medicine and Biology, 2019)
The present study was carried out to determine the oral fluid pH in children with enamel resistant to dental caries, conditionally resistant enamel and caries susceptible enamel, and to determine the correlation between the oral fluid pH, DMF index and index of oral hygiene (HI). The study was performed on 7, 12 and 15-year-old healthy-looking children from Lviv (Ukraine). The sample population consists of 292 male and female ones. Dental caries was recorded using DMFT (Decayed, Missed, and Filled Teeth) index. Structural and functional resistance of the tooth enamel was determined by the express-method (TER-test - test of enamel resistance), suggested by V.R. Okushko (1983) in our modification. The salivary pH was measured using pH indicating paper. It was found that in children with enamel, resistant to carious process, (TER=2,26±0,19 points) oral fluid reaction is slightly alkaline (pH=7,08±0,06 units), the lowest values of caries intensity of the permanent teeth and oral hygiene index (DMF=1,51±0,16 tooth, GI=1,55±0,21 points) were established. In group of children with conditionally resistant enamel (TER=4,28±0,10 points) the insignificant shift was detected in the oral fluid pH towards the acidic side (6,95±0,05 units), the average mean of hygienic index was 1,64±0,24 points (satisfactory hygiene) and DMF=2,43±0,19 tooth. It was found that children with caries susceptible enamel demonstrated the high level of the permanent teeth caries intensity (DMF=5,68±0,19 teeth), poor oral hygiene (GI=2,13±0,24 points), shift of the oral fluid pH towards the acid side (6,35±0,07 units), that changes the function of oral fluid toward demineralizing solution (TER=6,25±0,23 points). The physical properties of oral fluid, such as pH, have a correlation with dental caries activity and enamel resistance in children.
Keywords: enamel resistance; dental caries; DMFS; oral fluid pH